Pengaruh Komunikasi dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Pada Dinas Perindustrian dan Perdagangan Kabupaten Bima - Leni Kusumawati; Firmansyah Kusumayadi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This research is an associative research which aims to determine the effect of communication and work motivation on employee job satisfaction at the Department of Industry and Trade of Bima Regency. This research was conducted at the Department of Industry and Trade of Bima Regency. The research instrument used was a questionnaire containing a number of statements using a Likert scale measurement. The population used is all employees at the Department of Industry and Trade of Bima Regency. as many as 56 employees. The sampling technique used purposive sampling with a total sample of 49 ASNs. Data collection techniques used in this research are observation, interviews, documentation, literature study. Data analysis techniques used were validity test, reliability test, multiple linear regression, correlation coefficient, coefficient of determination, t test, F test. The results showed that communication and work motivation affect employee job satisfaction in the Department of Industry and Trade of Bima Regency. The magnitude of the influence of communication and work motivation on employee job satisfaction at the Department of Industry and Trade of Bima Regency. by 69.2%.